2012
DOI: 10.1128/cvi.00354-12
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Clumping Factor A-Containing Vaccine Induces Functional Antibodies to Staphylococcus aureus That Are Not Observed after Natural Exposure

Abstract: Staphylococcus aureus is a Gram-positive pathogen that causes devastating disease and whose pathogenesis is dependent on interactions with host cell factors. Staphylococcal clumping factor A (ClfA) is a highly conserved fibrinogen (Fg)-binding protein and virulence factor that contributes to host tissue adhesion and initiation of infection. ClfA is being investigated as a possible component of a staphylococcal vaccine. We report the development of an Fg-binding assay that is specific for ClfA-mediated binding.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…7,40-43 For example, a recent publication has shown that higher levels of preexisting antibodies against S. aureus toxins (including α-hemolysin) are associated with a lower risk of sepsis in patients with S. aureus bacteremia, 44 while another group has shown that naturally occurring antibodies against clumping factor A, another established staphylococcal virulence factor, are not functional and unable to prevent binding to the cognate host target fibrinogen. 45 To further explore the role of preexisting antibodies against S. aureus molecules, we isolated and characterized LTM14, an antibody against α-hemolysin from a human donor library. LTM14 binds α-hemolysin with very high affinity (1.7 pM), which is unusual for an antibody derived from a phage display library.…”
Section: Discussionmentioning
confidence: 99%
“…7,40-43 For example, a recent publication has shown that higher levels of preexisting antibodies against S. aureus toxins (including α-hemolysin) are associated with a lower risk of sepsis in patients with S. aureus bacteremia, 44 while another group has shown that naturally occurring antibodies against clumping factor A, another established staphylococcal virulence factor, are not functional and unable to prevent binding to the cognate host target fibrinogen. 45 To further explore the role of preexisting antibodies against S. aureus molecules, we isolated and characterized LTM14, an antibody against α-hemolysin from a human donor library. LTM14 binds α-hemolysin with very high affinity (1.7 pM), which is unusual for an antibody derived from a phage display library.…”
Section: Discussionmentioning
confidence: 99%
“…High anti-ClfA antibody levels have also been observed during natural infections with S. aureus, but their presence did not correlate with protection against infection 21 and it has been shown that contrarily to vaccine-induced antibodies, they do not block ClfA binding to fibrinogen. 68 Passive and active immunization strategies relying on antibodies targeting one single virulence factor to prevent S. aureus infection have failed to date, suggesting the need to consider multicomponent vaccines and a possible role for T-cell-mediated immune response. 22 Th17 lymphocytes play an important role in the immunity against S. aureus skin or lung infections in mice via IL-17 production, which plays a key role in neutrophil recruitment and in the activation of keratinocytes and mucosal cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, antibodies against PVL were not associated with protection in children with SSTI (36). Anti-clumping factor A antibodies elicited by vaccination were functional, but not those elicited by natural infection (37), suggesting that antibody function may be uncoupled from immunogenicity. Therefore, it is likely that protective immunity in patients also requires a specific repertoire of functional anti- bodies, and our studies point to the need for high titers of IgG recognizing saeRS-regulated antigens as being critical for protection.…”
Section: Discussionmentioning
confidence: 99%